GERMINATION AND DORMANCY IN SEEDS OF Sorghum halepense AND Sorghum arundinaceum - Krenchinski, F. H.; Albrecht, A. J. P.; Albrecht, L. P.; Villetti, H. L.; Orso, G.; Barroso, A. A. M. [UNESP]; Victoria Filho, R. (Univ Federal Vicosa, 2015)
Light, temperature and dormancy are factors that influence the germination of seeds and are strictly linked to the emergence of weeds. The objective of this work was to assess the germination of Sorghum arundinaceum and Sorghum halepense subjected to different conditions of temperature and luminosity, as well as assessing seed dormancy breaking mechanisms. For this, two experiments were conducted, both arranged in a completely randomized design. Experiment 1 was installed in a 2 x 5 double factorial design. The first factor was the absence or presence of light for 12 hours, and the other was composed of five constant temperatures: 15, 20, 30, 40 and 45 degrees C. In experiment 2, the efficiency of nine treatments used for breaking dormancy of seeds was assessed. The variables analyzed for both experiments were germination percentage and germination speed index (GSI). For the statistical analysis were performed an analysis of variance (ANOVA) and all the necessary consequences, as well as regression, when relevant. In experiment 1 for both species greater germination occurred in the presence of light. For S. arundinaceum the temperatures at which there was the highest percentage of germination were 33.13 and 31.24 degrees C for presence and absence of light respectively. As for S. halepense these temperatures were 31.98 and 29.75 degrees C for presence and absence of light respectively. As for the treatments for breaking dormancy, the mechanical scarification of seeds with sandpaper presented the highest germination and GSI. It is concluded that the Sorghum species studied are neutral photoblastic seeds and present mechanical type dormancy.
Keywords: johnsongrass; false johnsongrass; dormancy; seeds